Impact of Delayed Presentation on the Surgical Outcome of Epidural Hematoma in Traumatic Brain Injury Patients - Arshad Iqbal, Taimoor Ali, Muhammad Anwarullah, Qazi Ziaullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To note the impact of delayed presentation on the surgical outcome of extradural hematoma in traumatic brain injury. Study Design: A case-series study. Place Duration of the Study: Department of Neurosurgery, Lady Reading Hospital Peshawar from July 2018 to June 2019. Methodology: A total of 119 patients of both genders aged 15-45 years suffering from epidural hematoma with history of head trauma presented after 6 hours having size of hematoma above 30 ml (as per axial images of CT brain) were included. Frequency of favorable and unfavorable outcomes were noted after three months of follow-up. Outcome was termed as favorable if patient had good recover or moderate disability. Results: Out of total 119 patients, 89 (74.8%) were male. Unfavorable outcome was noted in 37.8% (n=45) of total patients with delayed presentation to the hospital, while favorable outcome was noted in 62.2% (n=74) of patients. Good recovery and moderate disability were observed in 27.7% (n=31) and 34.5% (n=41) of total patients respectively. While, severe disability and vegetative state was recorded in 26.1% (n=31) and 7.6% (n=9) of patients respectively. Practical Implications: Efforts should be made to increase awareness about timely presentation and interventions for better surgical outcomes among patients of extradural hematoma. Conclusion: Frequency of unfavorable surgical outcome of extradural hematoma found to be 37.8% in head trauma patients with late presentation. Keywords: Extradural Hematoma, Glasgow Coma scale, surgical outcome